Sick societies responding to the global challenge of chronic disease - Stuckler, David; Siegel, Karen (Oxford : Oxford University Press, 2011)
Chronic diseases are the leading causes of death and disability worldwide, and are expected to increase over the coming years with the ageing population and improved medical treatments that reduce mortality but cause the sufferer to live with a long-term illness. This book provides the first comprehensive review of the topic.
Also issued in print format.
Description based on online resource; title from PDF title page (viewed on Jan. 20, 2012).
Keywords: Chronic diseases -- Epidemiology